Social Support and Suicide Risk Among Chinese University Students: A Mental Health Perspective - Chu, Haiyun; Yang, Yanjie; Zhou, Jiawei; Wang, Wenbo; Qiu, Xiaohui; Yang, Xiuxian; Qiao, Zhengxue; Song, Xuejia; Zhao, Erying (Frontiers in Public Health, 2021)
Background World Health Organization recognizes suicide as a public health priority. This study aimed to investigate the risk life events which led university students to consider suicide and explore the protective mechanism of social support (including subjective support, objective support, and support utilization) on suicide risk. Methods 3972 university students were recruited in Harbin, China. Social Support Rating Scale, Self-Rating Anxiety Scale, the Beck Depression Inventory, and the 25-item scale of suicide acceptability were used to collect participants’ information. Descriptive statistics, Pearson’s correlation, and mediation analysis were employed for statistical analysis. Results “Drug addict”, “infected with HIV”, and “incurable illness” were the top three events that led university students to consider suicide. Social support played an important protective role against suicide risk. Subjective support and support utilization had total effects on suicide acceptability, including direct and indirect effects. Anxiety (indirect effect = -0.022 , 95% CI= -0.037 -0.009) and depressive symptoms (indirect effect = -0.197, 95% CI= -0.228 -0.163) mediated the relationship between subjective support and suicide acceptability; meanwhile, the association between support utilization and suicide acceptability was mediated by anxiety (indirect effect = -0.054, 95% CI=-0.088 -0.024) and depressive symptoms (indirect effect =-0.486, 95% CI=-0.558 -0.422). However, the protective impact of objective support worked totally through decreasing anxiety (indirect effect =-0.018, 95% CI=-0.035 -0.006) and depressive symptoms (indirect effect = -0.196, 95% CI= -0.246 -0.143). Moreover, the mediation effects of depressive symptoms had stronger power than anxiety in the impact of social support on suicide risk. Conclusions Among Chinese university students, suicide acceptability was elevated when there was a health scare. Social support effectively reduced suicide risk via decreasing anxiety and depressive symptoms. From the mental health perspective, families, peers, teachers, and communities should work together to establish a better social support system for university students, if necessary, help them to seek professional psychological services.